Finance and Development, December 2007. (Finance and Development; Finance and Development ;, 2007)
'Global Governance: Who's in Charge?' examines the challenges-financial, health, environmental, and trade-facing the international community in the 21st century and asks whether today';s system of global governance is equipped to cope with them. The lead article asserts that the system that served as a model for much of the 20th century is out of date, and it explores what needs to be done to strengthen it. Other articles on this theme look at the recent U.S. subprime market crisis, the differences between financial crises of the 19th and 20th centuries and what future crises will look like, the need for a stronger system of multilateral trade, and how global health threats can be handled. 'People in Economics' profiles Michael Kremer; 'Picture This' describes the changing aid landscape; 'Country Focus' spotlights the United Arab Emirates; and 'Straight Talk' examines the impact of high food prices. Also in this issue, articles examine development in Africa, and 'backcasting' data in Latin America.